Advances in Product Family and Product Platform Design Methods & Applications - Simpson, Timothy W.; Simpson, Timothy W.; Jiao, Jianxin (Roger).; Jiao, Jianxin (Roger).; Siddique, Zahed.; Siddique, Zahed.; Hölttä-Otto, Katja.; Hölttä-Otto, Katja. (Springer New York : Imprint: Springer, 2014)
Advances in Product Family and Product Platform Design: Methods & Applications highlights recent advances that have been made to support product family and product platform design and successful applications in industry. This book provides not only motivation for product family and product platform design—the “why” and “when” of platforming—but also methods and tools to support the design and development of families of products based on shared platforms—the “what”, “how”, and “where” of platforming. It begins with an overview of recent product family design research to introduce readers to the breadth of the topic and progresses to more detailed topics and design theory to help designers, engineers, and project managers plan, architect, and implement platform-based product development strategies in their companies. This book also: Presents state-of-the-art methods and tools for product family and product platform design Adopts an integrated, systems view on product family and product platform design Details successful applications and case studies from a variety of industries Combines contributions from leading experts from industry as well as academia Is accessible to novice practitioners as well as experienced designers and engineers Advances in Product Family and Product Platform Design: Methods & Applications is an ideal book for designers, engineers, and project managers working in the field of product design as well as students, faculty, and researchers wanting to learn more about the latest work in the area.